Validity of subjective smoking status in orthopedic patients - Bender D; Haubruck P; Boxriker S; Korff S; Schmidmaier G; Moghaddam A (Dove Medical Press, 2015)
Daniel Bender,* Patrick Haubruck,* Sonja Boxriker, Sebastian Korff, Gerhard Schmidmaier, Arash Moghaddam Trauma and Reconstructive Surgery, Center for Orthopedics, Trauma Surgery and Spinal Cord Injury, Heidelberg University Hospital, Heidelberg, Germany *These authors contributed equally to this work Purpose: In this level 1 diagnostic study, we analyzed the validity of subjective smoking status and, as secondary research question, the smoking cessation adherence in orthopedic patients during a routine hospital stay of nonunion patients by measuring serum cotinine.  Methods: We included patients undergoing revision surgery due to nonunion of long bones. Patients were interviewed about their smoking status. Blood samples were taken from all the patients prior to surgery and for an additional 6 weeks following surgery. Serum levels of cotinine were measured, and coherence between subjective smoking status and objective cotinine analysis was evaluated.  Results: Between March 2012 and August 2014, we enrolled 136 patients. Six of the 26 “previous smokers” (23%) and four of the 65 “nonsmokers” (6%) had serum cotinine above cutoff levels. In self-labeled smokers, serum cotinine levels averaged at 2,367.4±14,885.9 ng/mL (with a median of 100 ng/mL), whereas in previous smokers the levels averaged at 4,270±19,619.4 ng/mL (with a median of 0 ng/mL) and in the nonsmokers group the levels averaged at 12±53.9 ng/mL (with a median of 0.03 ng/mL). Overall, the subjective smoking status matched serum cotinine testing in 88% of the cases. Sensitivity was 79.6% and specificity was 93.1%. Ninety-one percent of the patients with preoperative positive serum values were still positive at follow-up.  Conclusion: In this study, we could show that subjective smoking status in orthopedic patients is predominantly reliable as validated by objective cotinine measurements; however, patients who declare themselves as “previous smokers” are at elevated risk for underreporting continued smoking and patients who smoked preoperatively are at high risk for continuing their habit. In the future, caregivers should consider introducing effective treatments for smoking cessation to smokers and furthermore offer effective treatments to maintain smoking cessation in previous smokers during their routine consultation prior to orthopedic and trauma surgery. Keywords: smoking, cotinine, nonunion, smoking behavior, smoking cessation, risk evaluation